1998
DOI: 10.1111/j.1469-1795.1998.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Bats and insects over two Scottish rivers with contrasting nitrate status

Abstract: The abundance of foraging bats (Pipistrellus pipistrellus and Myotis daubentonii) and flying insects over two rivers in north-east Scotland (Dee and Ythan), differing eightfold in nitrate levels, were compared by paired samples over three periods in summer 1995, during each of which 10 nights' sampling was undertaken using ultrasonic detectors and insect suction traps. Thirteen out of the 18 pairwise comparisons of bat passes, insect numbers, biomass and diversity were not significantly different. The oligotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Some bat species (Pipistrellus pipistrellus, Eptesicus serotinus and Myotis sp.) respond to the presence of cattle, presumably because presence of dung increases the amount of available nutrients that promote the development of invertebrates on which bats feed (Shiel et al, 1991;Robinson and Stebbings, 1993;Racey et al, 1998). It is possible as well that the animals themselves disturb ground insects while they graze, facilitating predation by bats (Downs and Sanderson, 2010).…”
Section: Bat Activity Over Pondsmentioning
confidence: 97%
“…Some bat species (Pipistrellus pipistrellus, Eptesicus serotinus and Myotis sp.) respond to the presence of cattle, presumably because presence of dung increases the amount of available nutrients that promote the development of invertebrates on which bats feed (Shiel et al, 1991;Robinson and Stebbings, 1993;Racey et al, 1998). It is possible as well that the animals themselves disturb ground insects while they graze, facilitating predation by bats (Downs and Sanderson, 2010).…”
Section: Bat Activity Over Pondsmentioning
confidence: 97%
“…In a study designed to test this hypothesis, Racey et al (1998) found little difference between the numbers of bats and insects foraging over a small eutrophic river and a large oligotrophic one. Park & Cristinacce (2006) investigated the effect on foraging bats of phasing out percolating filter beds, which provide breeding opportunities for dipterans, in favour of activated sludge, for treating human sewage.…”
Section: Concentrations Of Other Heavy Metals and Toxic Elements Havementioning
confidence: 99%
“…860% (Kokurewicz, 1995). This population growth may reflect the increased availability of insect prey, notably midges (Diptera: Chironomidae), caused by eutrophication processes (Kokurewicz, 1995;Racey et al, 1998). In that context the decline in the maximal number of bats observed in the mine exceeding 19% is most probably the real effect of disturbance.…”
Section: Survival and Effect Of Disturbancementioning
confidence: 99%